Ethan Allen style create the look you love - Samon, Katherine Ann; Allen, Ethan ([Place of publication not identified] Ethan Allen Marketing Corporation, 2002)
Create the look you love! How do you create rooms you'll love living in every day? Just look inside, Ethan Allen's design team has compiled more than twenty beautiful and distinct styles, each with pages of richly detailed photographs, filled with inspiration and information on design and history to help you-step by step-realize the looks you've dreamed of.
American formal (Formal mix -- Townhouse style -- Gracious living -- Period house -- American eclectic) -- European classics (Island influences -- Tuscany story -- Swedish country -- British travel -- Euro eclectic) -- Contemporary living (Urban country -- Penthouse view -- Loft living -- Retro modern -- Zen palette) -- Casual country (Simple charm -- Vintage mix -- Ski lodge -- First home -- Beach house) -- Kids' stuff.
Keywords: Interior decoration -- United States